Ngân hàng bài tập
A

Hàm số $y=\dfrac{\left(x-2\right)^2}{1-x}$ có đạo hàm là

$y'=-2\left(x-2\right)$
$y'=\dfrac{x^2+2x}{\left(1-x\right)^2}$
$y'=\dfrac{-x^2+2x}{\left(1-x\right)^2}$
$y'=\dfrac{x^2-2x}{\left(1-x\right)^2}$
1 lời giải Huỳnh Phú Sĩ
Trở lại Tương tự
Thêm lời giải
1 lời giải
Huỳnh Phú Sĩ
20:37 17/01/2022

Chọn phương án C.

$\begin{aligned}
y'&=\dfrac{2\left(x-2\right)\left(1-x\right)-\left(x-2\right)^2\left(-1\right)}{\left(1-x\right)^2}\\
&=\dfrac{-x^2+2x}{\left(1-x\right)^2}.
\end{aligned}$